First baseline for bioenergetic biomarkers in Cnesterodon decemmaculatus as test organism in ecotoxicological studies - Baudou, Federico Gastón (2020)
Cnesterodon decemmaculatus is a Neotropical teleost fish frequently used in ecotoxicological evaluations, whose biology has been thoroughly studied. Although there is considerable information on its response to different toxicants, no range of reference values has been so far established for the different biological parameters proposed as biomarkers of effect or exposure. Moreover, no study has yet examined the possible influence of the metabolic status of the exposed animals on their response to toxic stress. Therefore, the aim of this work was to provide a first baseline for a set of bioenergetic biomarkers in C. decemmaculatus adults exposed to a control medium under previously standardized conditions, and to assess their possible intrinsic seasonal variability. The responses of the biomarkers obtained from the controls were contrasted with those from the reference toxicant (Cadmio-Cd) and receiving waters (surface waters of the Reconquista River RR, Buenos Aires Province, Argentina). We conducted four 12-day assays (one in each season) of exposure to control media, (reconstituted moderate hard water, MHW) and two assays of exposure to Cd in MHW and surface river water (RR) in both summer and autumn. The variables recorded were: Food intake (In), fecal production (F), specific assimilation (A) and cumulative mortality, oxygen extraction efficiency (OEE), specific metabolic rate (SMR), ammonia excretion (N), ammonia quotient (AQ) and scope for growth (SFG). The seasonal variation shown by some physiological parameters, points to the need for establishing a baseline obtained from standardized media, preferably on a seasonal basis. Moreover, SFG and A appeared as the most sensitive biomarkers, emphasizing the importance to consider the metabolic status of the test organisms for the appropriate interpretation of results from ecotoxicological studies performed under controlled experimental conditions. The obtained results provide useful information on C. decemmaculatus as model species in ecotoxicological bioassays involving biomarkers of early effect.